Strategi Pengembangan Usaha UMKM “Aiko Frozen Food” Desa Jatirejo, Kec. Suruh Kab. Semarang - Shabrinaya Jenny Maheswari; Davin Ghifari Septananda; Ray Alha Lataza Sakti Jo; Novianti Dwi Larviatma; Luh Ayu Rengganis Putri; Eva Kurnila; Satria Wira Darma; Maria Entina Puspita (STIE Pelita Nusantara, 2026)
This community service program is designed to improve the capabilities of Aiko Snack & Frozen Food MSMEs located in Jatirejo Village, Suruh District, Semarang Regency through comprehensive business support. The program emphasizes improving production processes, strengthening business legality, financial management, digital promotion, and brand development. The approach used includes field observations, interview sessions, direct production assistance, visual identity development, licensing assistance, basic bookkeeping training, and project-based learning guidance. The results show that MSME owners have succeeded in improving production efficiency and product quality through standardized processing, hygiene practices, and good packaging. Brand development, such as logo design and product menu development, has successfully increased brand visibility and appeal to consumers. Support in obtaining a Business Identification Number (NIB), halal certification, and a Home Industry Food Production Permit (PIRT) has also strengthened business credibility and customer trust. In the area of financial management, owners implemented simple bookkeeping by separating personal and business finances, enabling more transparent cash flow monitoring and clear profit identification. Furthermore, digital promotion through the Instagram platform expanded market reach beyond the previous WhatsApp-based promotion strategy. Overall, this program has been successful.